A review on the internationalisation of emerging market SMEs - Buyukbalci, Pinar; Urfa, Ayse Merve; Can, Esin (SPRINGERNATURE, 2025)
Albeit SME internationalisation has attracted considerable attention recently, our knowledge of studies researching emerging market SMEs is limited. Considering that emerging markets are critical actors in reshaping global business, the current study portrays what researchers wonder about the internationalisation process of emerging market SMEs (EM-SMEs). In this context, we conducted a systematic literature review covering studies in Web of Science between 2003 and 2022. The papers were subject to review concerning the following criteria: (1) main objective and type of research; (2) theoretical framework/s; (3) methodological issues; and (4) main variables, findings, and conclusions. Following our review, we present a research agenda addressing promising future streams by highlighting the impact of (i) research design, (ii) individual-level factors, (iii) firm-level factors, (iv) macro-level factors, and (v) emerging market factors. We also present a conceptual model to better reflect on the current debate.
Keywords: Internationalisation; Emerging market; Small and medium sized Enterprise; Entrepreneurship; New ventures; Literature review; BORN GLOBAL FIRMS; DYNAMIC CAPABILITIES; MEDIATING ROLE; VENTURE INTERNATIONALIZATION; ENTREPRENEURIAL PROCLIVITY; KNOWLEDGE DEVELOPMENT; QUALITATIVE RESEARCH; MEDIUM ENTERPRISES; BUSINESS RESEARCH; FOREIGN-MARKETS; Business & Economics